Persepsi pekerja orang kurang upaya terhadap perkembangan kerjaya di dalam organisasi - Mohd Safiq, Bin Latip (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Class of persons with disabilities (PWDs) is a minority that has received increasing attention over some successes that have been created. People are also increasingly paying attention to this group. Their success has opened the eyes of the public will be incredible inner strength that they have. They have performed well in careers. In other words, the disabled are also able to do the job and it is closely related to justice in organizations where disabled people work and perception of disabled people themselves limitations. This study aimed to understand the perceptions of people with disabilities who are working on the development of their careers within the organization, especially in Malaysia. This study attempts to examine and identify the two variables, namely 1) the relationship between the organization factor and 2) the relationship between internal factors perception of disabled people to the career development of disabled people in the organization. The study was conducted through qualitative methods involving five informants working disabled persons. In-depth interviews conducted to obtain the necessary information. The results showed an average informant working disabled persons found to play an important role in enhancing their career development. The study concludes with some suggestions from researchers submitted to the disabled, community, employers and authorities.